Financial leverage in a post-pandemic scenario: a case study in a packaging industry - Aladic, Erica Marques; Silva, Jailson dos Santos; Oliveira, Jeffson Veríssimo de (Brazilian Journal of Production Engineering, 2024)
During the Covid-19 pandemic, some companies, such as those in the packaging sector, experienced financial leverage, increasing their margins. However, the post-pandemic period saw these numbers decrease, returning to the average monthly amount. Thus, the aim of this study is to propose a set of financial leverage strategies to boost profitability in a packaging industry. The results highlight the need to consider pricing aspects by passing on costs and adjusting contracts according to the inflation of key raw materials, seeking new clients, and becoming more competitive, thereby maintaining and/or accelerating margins. Additionally, it was observed that there could be long-term investment in new expansion projects (joint ventures) and investments in ESG to sustain financial leverage. These actions are expected to help increase the company's profitability and make it more competitive in the market.
Keywords: Covid-19; EBITDA; strategy; profitability